A Motivational Interviewing Course for Pharmacy Students - Goggin, Kathy (American Journal of Pharmaceutical Education, 2010)
OBJECTIVE: To create, implement, and evaluate a pharmacy course on motivational interviewing. DESIGN: A 3-hour elective course was created to train doctor of pharmacy (PharmD) students in brief patient-centered motivational interviewing counseling strategies that have proven effective with the types of health issues most commonly addressed in pharmacy settings. Students were assisted in developing their skills through required readings, interactive lectures, in-class demonstrations and practice sessions, out of class skills practice, one-on-one supervision provided by doctoral level clinical health psychology students, and written reflections on each class session. ASSESSMENT: Students demonstrated significant improvement in motivational interviewing skills and a high level of motivation for and confidence in using these skills in their future practice. Students overall assessment of the course and supervision process was highly positive. CONCLUSION: This patient-centered counseling skills course was feasible and produced improvements in PharmD students' counseling skills and increased their motivation and confidence to use motivational interviewing skills in their future communications with patients.